Vegetation diversity in the Geumpang Protected Forest Area, Pidie District, Aceh, Indonesia - ASHABUL ANHAR; GINA ERIDA; ASTRI WINDA SIREGAR; HANIFA RAHMAH; ALI M. MUSLIH; ILHAM HANAFI; DURRAH HAYATI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Anhar A, Erida G, Siregar AW, Rahmah H, Muslih AM, Hanafi I, Hayati D. 2025. Vegetation diversity in the Geumpang Protected Forest Area, Pidie District, Aceh, Indonesia. Biodiversitas 26: 4490-4499. Forests, as complex ecosystems, play a vital role in maintaining global environmental balance by providing critical ecosystem services such as biodiversity conservation, climate regulation, and water management. The Geumpang Protected Forest Area (PFA) in Pidie District, Aceh, Indonesia, is a key area for ecological stability and community benefits, making biodiversity research essential to inform conservation efforts and sustainable forest management policies. The research was conducted in the Geumpang PFA. This study employed vegetation analysis techniques with 63 plots of varying sizes established to collect data on species, individual counts, stem diameters, and tree heights. Data analysis included indices for diameter distribution, Importance Value Index (IVI), species dominance (C), species diversity (H'), evenness (E), and richness (R) to assess forest composition and structure. The results highlighted species composition across growth stages, with indices providing insights into dominance, diversity, and distribution patterns within the forest ecosystem. The Geumpang PFA contains a wide variety of vegetation diversity, comprising 14 species at the seedling stage, 30 species at the sapling stage, 32 species at the pole stage, and 39 species at the tree stage, with a total of 46 vegetation species across all growth stages. The tree diameter distribution in the Geumpang PFA forms an inverted J-shaped curve. The highest IVI is recorded for Lithocarpus sp. in tree (77.18%) and pole (32.92%) stages, Ficus hispida in sapling stage (24.83%), and Coffea canephora in seedling stage (65.43%). In general, the C in Geumpang PFA is low across all growth stages, with values approaching 0. The H’ ranges from medium to high, with a high value in the pole stage (3.12) and medium values in the tree, sapling, and seedling stages (2.94, 2.89, and 2.10, respectively). The E shows the pole stage with the highest value (0.90) and the seedling stage with the lowest (0.79). The R shows high species richness at the tree (R: 6.31), pole (R: 5.77), and sapling stages (R: 5.28), while the seedling stage has low richness (R: 2.86). The high vegetation diversity and early-stage regeneration challenges in the Geumpang PFA underscore the urgent need for conservation succession, ecosystem resilience, and local community benefits.